Restriction of Antimicrobial Usage in a Tertiary Care Neonatal Unit in South India: A Before After Trial - V N S Sowjanya, S; Venugopalan, Lakshmi (International Journal of Neonatology, 2020)
Background Overuse and abuse of antibiotics resulted in emergence of multidrug-resistant organisms (MDRO), increased rates of invasive candidiasis, prolonged hospital stay, NEC (Necrotizing enterocolitis), LOS (Late onset sepsis) or death. Restriction of the prescription, switching to a narrower spectrum and stopping antibiotics when not needed are some of the major approaches to antibiotic stewardship. Methods We identified restricted antimicrobials and devised an antimicrobial justification form. Clinicians needed to fill the form before prescribing restricted antimicrobials thereby comparing the antimicrobial usage pattern before and after the introduction of form. Babies enrolled before the introduction of the justification form were labelled as Group 1, and as Group 2 after justification form. The HIC (hospital infection control) staff nurse paid daily visits to NICU to monitor number of babies started on restricted antibiotics and whether the forms were duly filled or not. Any lag would be intimated to the Head HIC team for rectification. Any change of antibiotic within the restricted group also warranted justification. Culture report notified within 48 – 72 hrs so as to facilitate the stoppage of antibiotics in case of negative culture. Results There was a statistically significant reduction in the usage of restricted antimicrobials in the Group B as compared to Group A 150 (40.54%) vs 190 (49.35%) (p = 0.01). There was a statistically significant increase in the % of babies de-escalated from high end antimicrobials in Group B as compared to Group A 90 (60%) vs 56 (29.47%) (p = <0.0001). Duration of restricted antimicrobials reduced from 13.78 ± 2.7 days in Group A to 9.9 ±1.8 days in Group B (p = <0.0001). No difference in the number of babies started on any antibiotic between both the groups (p = 0.1). Conclusion Introduction of the antibiotic justification form as a part of antimicrobial stewardship program resulted in an overall reduced usage of restricted antimicrobials along with rapid de-escalation.
Keywords: Antibiotics; De-escalation; Justification; Multidrug resistant; NICU; and Stewardship.